MEMBANGUN BRAND IMAGE SEBAGAI MANAJEMEN STRATEGI DALAM UPAYA MENINGKATKAN DAYA SAING PADA LEMBAGA PENDIDIKAN - Junita Manurung; Harlyn L Siagian (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2021)
Significant changes to knowledge and technology in the modern era like today encourage changes in systems and governance in the field of education. Educational institutions that have good quality I n society will Build a brand image which is expected to make these educational institutions stronger and will encourage prospective students to choose these educational institutions. If producers are able to market their products well and sell well in the market, the quality of these educational institutions can provide satisfaction to consumers and can be said to be salable in the market. And educational institutions that are unable to sell their products will not exist because they are inferior to other educational institutions. Educational institutions should realize from an early age that they are service producers who have to build brands so that their products sell well in the market and are bought by consumers. Brand image has an important position for the sustainability of an educational institution that grows among competition between institutions. For that, an educational institution must be able to compete with other educational institutions. However, the facts that occur in the field show that there are still many educational institutions that have not realized and understood this, so that in the competition they face various difficulties, especially with private schools that have large capital and have a good brand image and are popular among the community. The results of this discussion can be concluded that it is not easy to build a positive brand image of educational institutions. Marketing education is not done for commercial purposes but rather to competition the quality of educational institutions' services for the community. The ways that educational institutions can do in marketing educational services so that their competitiveness increases are market identification, market segmentation, product differentiation, conducting marketing communications and providing the best possible educational institution services.